Implementasi Algoritma Random Forest dalam Pengukuran Kesiapan Transformasi Digital Desa Kaduwulung Menuju Desa Cerdas Berbasis SNI ISO 37122:2019 - Esa Firmansyah; Muhammad Agreindra Helmiawan; Dody Herdiana; Dwi Yuniarto (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
The readiness of healthcare workers and village officials in adopting digital technology is a decisive factor for the success of transforming into a smart village. This study aims to measure the digital transformation readiness level of Kaduwulung Village using the SNI ISO 37122:2019 standard through village data mapping and the implementation of the Random Forest algorithm for digital maturity classification. The research methodology employs a quantitative approach using the Design Thinking model combined with the Technology Acceptance Model (TAM) evaluation. The design results demonstrate that the integration of automated scoring features can assist in faster decision-making for public services. Based on the testing, the system obtained a System Usability Scale (SUS) score of 74 and a User Experience Questionnaire (UEQ) score of 1.98, proving that technology adoption readiness is significantly influenced by ease of navigation and system infrastructure support.